Antimicrobials in polymethylmethacrylate: from prevention to prosthetic joint infection treatment: basic principles and risk of resistance - Marta Sabater-Martos; Miguel A. Verdejo; Laura Morata; Ernesto Muñoz-Mahamud; Ernesto Guerra-Farfan; Juan C. Martinez-Pastor; Alex Soriano (Arthroplasty, 2023)
Abstract Background Excellent revisions about antibiotic-loaded bone cement (ALBC) have been recently published. In the present article, we review the principles and limitations of local antibiotic delivery in the context of recent advances in the pathogenesis of prosthetic joint infections (PJI), with particular attention paid to the potential association between ALBC and antimicrobial resistance. Main body Recalcitrance of PJI is related to the ability of pathogens to adapt to particular environments present in bone tissue and protect themselves from host immunity in different ways. Accordingly, delivery of high local antimicrobial concentrations using ALBC is needed. Most relevant clinical data showing the efficacy of ALBC for PJI prophylaxis and treatment are reviewed, and we dissected the limitations on the basis of the recent findings from animal models and suggested that aminoglycosides, in particular, could not be the best option. One of the major concerns associated with ALBC is the emergence of resistance because of theoretical prolonged exposure to low antibiotic concentrations. We summarize the mechanisms for the selection of resistant microorganisms, and we critically reviewed the evidence from animal models and clinical data from observational and registry studies and concluded that there is no evidence to support this association. Conclusion While waiting for better evidence from well-designed clinical trials, ALBC shows a beneficial effect as a prophylaxis in arthroplasty, and to avoid the colonization of spacers used for two-stage revision in patients with PJI. Experimental models and clinical evidence suggest the need to achieve high local antimicrobial concentrations to obtain the highest prophylactic and therapeutic effect. The current evidence does not support the risk of increasing resistance with use of ALBC. In the future, it is necessary to evaluate new carriers and different antimicrobials to improve clinical outcomes.